Neuroleadership A Journey Through the Brain for Business Leaders - Ghadiri, Argang. (Management for Professionals,, 2012)
This book takes you on a journey through the brain, its function and its impact on leadership. The young business field of neuroleadership is founded on the belief that understanding the brain can give leaders new and powerful insights into human behaviour and how to effectively tap into that knowledge to generate better returns in business. The book approaches the background, history, and major thinkers in the field, but also reassesses the fundamental concept of neuroleadership. The authors look into the fundamental basic needs of human beings, how they are represented in the neural networks, and how this manifests in motivational drives. The book also focuses explicitly on how impactful organisational tools can be from the viewpoint of the brain. By following this methodology, the reader will be able to use the knowledge of neuroscience at the workplace to better address individuals’ brains and hence tap into the full power of brains in business.